Förekomst och grad av osteokondros i distala radius och ulna hos konventionellt och KRAV-uppfödda slaktsvin - Ólafsdóttir, Lísa (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2006)
The occurrence and degree of osteochondrosis was studied in 64 pigs raised in conventional systems (45) or organically according to KRAVs principles (19). In this blind study the growth plates of distal radius and ulna were examined macroscopically and radiologically searching for pathological lesions. One significant difference was shown in this study. Conventionally raised pigs diagnosed with osteochondrosis had more severe lesions in the distal growth plate of radius and ulna than the corresponding group of pigs raised organically. No significant difference was shown between the groups when all pigs were included.